Inhibitory effect of the methanolic fraction of Oxapampa propolis on different isolated genotypes of Streptococcus mutans in children with caries - Vargas Gil, Mayra Lizeth (2024)
Objective: To determine the inhibitory effect of the methanolic fraction of propolis from Oxapampa, Peru, on different genotypes of Streptococcus mutans in children diagnosed with caries. Materials and methods: 150 oral swab samples were collected, seeded for isolation of S. mutans and then identified by biochemical tests of carbohydrate fermentation, Api 20 Strep (bioMérieux) and conventional PCR. The 138 strains isolated and identified from patients and the S. mutans ATCC® 25175™ control were confronted with the methanolic fraction by the disk diffusion method, having as positive control 0.12% chlorhexidine and negative control Milli-Q water and DMSO (1:1). Results: It was found that the inhibition diameter of the strains extracted from children diagnosed with caries against the methanolic fraction showed greater diameter (14.13 mm) in relation to the strain of S. mutans ATCC® 25175™ (10.16 mm) with statistically significant differences. In the genotyping of the 138 strains with the different specific primers (c, e, f, and k), it was found that 63.77% belonged to genotype c, 21.73% to genotypes c and e, and 14.50% to genotypes c and f. Conclusions: The methanolic fraction of Oxapampa propolis presents inhibitory activity on S. mutans strains isolated and genotyped in children diagnosed with caries. In addition, it presents greater inhibitory activity in strains obtained from children compared to S. mutans ATCC® 25175™.